Menyoal Hermeneutika Feminis terhadap Wacana Kesetaraan Gender - Sayyaf Nasrul Islami (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2022)
Until now, gender equality is still a hot topic for discussion among Muslim feminists. Via content analysis, this study tries not only to elaborate a number of products of the Hermeneutic model of the reinterpretation of the Koran the women's version but also shows the history of feminism ideology and the inappropriate use of hermeneutic interpretations. The initiators and advocates of gender equality often question Islamic law which is considered unfair in positioning men and women. Women are considered discriminated against by the products of Islamic law that have been established so far. From its historical background, feminism departs from the ideology of hatred as a form of resistance to the oppression of women that occurred in Western-Christian civilization in the past. Hermeneutic interpretation method also comes from the Christian academic tradition which considers the biblical text not as revelation. These two facts are diametrically opposed to the facts in the Islamic tradition. Islam actually came with the glory and majesty of its teachings. The change in the social position of women was no exception, which was more glorified when Islam changed the Arab civilization of ignorance at that time. The concept of equality is basically difficult to find in Islamic scholarship. Islam is more familiar with the term "justice" which is contained in the verses of the Qur'an and the hadiths of the Prophet Muhammad. So in this paper, the author finds the inappropriate use of feminist hermeneutics in interpreting the Qur'an and presenting the concept of justice in Islam which is more in line with Islamic tradition and scholarship.